The Lemonade reader - Brooks, Kinitra Dechaun; Martin, Kameelah L. 1978- (Routledge, an imprint of the Taylor & Francis Group, 2019)
The Lemonade Reader is an interdisciplinary collection that explores the nuances of Beyoncé's 2016 visual album, Lemonade. The essays and editorials present fresh, cutting-edge scholarship fueled by contemporary thoughts on film, material culture, religion, and black feminism. Envisioned as an educational tool to support and guide discussions of the visual album at postgraduate and undergraduate levels, The Lemonade Reader critiques Lemonade's multiple Afrodiasporic influences, visual aesthetics, narrative arc of grief and healing, and ethnomusicological reach. The essays, written by both scholars and popular bloggers, reflects a broad yet uniquely specific black feminist investigation into constructions of race, gender, spirituality, and southern identity. The Lemonade Reader gathers a newer generation of black feminist scholars to engage in intellectual discourse and confront the emotional labor around the Lemonade phenomena. It is the premiere source for examining Lemonade, a text that will continue to have a lasting impact on black women's studies and popular culture